The effect of optimal load training on punching ability in elite female boxers - Cui, Weijia; Chen, Yiming; Wang, Dexin (Frontiers in Physiology, 2024)
Optimal load training is a method of training that aims to maximize power output. This is achieved by arranging optimal loads (optimal ratios of load intensity and load volume) during strength training. The fixed load intensity and number of repetitions employed in traditional strength training. The present study will investigate the applicability of these two load arrangements to female elite boxers. Twenty-four elite female boxers were divided into three groups (optimal load [OL=8], traditional load [TL=8] and control group [CG=8]). The six-week intervention consisted of strength training with different loading arrangements. The punching ability and strength were tested before and after the intervention. We found that optimal load training enhances a boxer's punching ability and economy, which aligns with the demands of boxing and is suitable for high-level athletes, whose strength training loads require a more individualised and targeted approach.